2012
DOI: 10.1159/000342748
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status and Parathyroid Hormone Levels in Patients with Obstructive Sleep Apnea

Abstract: Background: Vitamin D insufficiency and high levels of parathyroid hormone (PTH) appear to be emerging risk factors for metabolic syndrome (MS), diabetes and cardiovascular disease, conditions that occur frequently in patients with obstructive sleep apnea syndrome (OSAS). Objectives: This study examined whether serum concentrations of 25-hydroxyvitamin D [25(OH)D] and PTH were associated with the presence of MS, diabetes and hypertension among an OSAS population. Methods: A total of 826 patients (635 men and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 38 publications
1
53
0
2
Order By: Relevance
“…[3][4][5][6] The novel contribution of the current study lies in the observation that a short-term treatment with nCPAP promotes the improvement of the vitamin D homeostasis in male patients with OSA. In fact, nCPAP is the treatment of choice to improve several internal parameters in patients with OSA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6] The novel contribution of the current study lies in the observation that a short-term treatment with nCPAP promotes the improvement of the vitamin D homeostasis in male patients with OSA. In fact, nCPAP is the treatment of choice to improve several internal parameters in patients with OSA.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] Vitamin D and PTH participate in bone metabolism and calcium homeostasis. Additionally, vitamin D has pleiotropic effects, modulating numerous metabolic processes in multiple tissues throughout the body.…”
mentioning
confidence: 99%
“…Whether elevated serum uric acid levels are associated with low 25(OH)D levels remains controversial. Whereas some published data indicate that elevated uric acid levels are inversely related to 25(OH)D levels (12), other studies have shown no such association (13). Thus, we aimed to investigate the potential association of serum uric acid and 25(OH)D levels.…”
Section: Introductionmentioning
confidence: 93%
“…[6][7][8] We and others have observed widespread vitamin D OSA. [9][10][11][12][13][14] Interestingly, 25(OH)D levels have been shown to be inversely correlated with OSA severity 10,11,13 and with metabolic alterations associated with OSA, including abnormal glucose metabolism 11,12 and nocturnal heart rate.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] A recent study suggested that the association between lower 25(OH) D and OSA was largely confounded by larger BMI and neck circumference. 9 In contrast, our group 10 and others [11][12][13][14] have reported a high rate of vitamin D deficiency in OSA, where vitamin D levels (25(OH)D) are lower in severe OSA 10,11,13 and inversely correlate with some of its associated metabolic alterations, including abnormal glucose metabolism 11,12 as well as nocturnal heart rate. 10 Vitamin D receptors are located systemically and recent advances have demonstrated the potential of vitamin D to influence a wide variety of organs.…”
mentioning
confidence: 83%